IMPLEMENTASI KEPEMIMPINAN PROFETIK DI SMA AL- WAROQOT PAMEKASAN: STUDI LIVING AL-QUR’AN DAN HADITS - Rozy, Fathorrozy; Halik, Abd (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
This article aims to describe the implementation of prophetic leadership at Al-Waroqot High School, Pamekasan, through a Living Qur'an and Hadith approach. Employing a qualitative method with a case study design, this research gathered data through in-depth interviews, participant observation, and documentary studies. The collected data were analyzed interactively through three stages: data condensation, data display, and conclusion drawing. The findings indicate that prophetic leadership is implemented by making the Qur'an and Hadith a living primary foundation within the school's culture. This practice is manifested through the exemplary roles of leaders and teachers who prioritize the values of justice and empathy, and it is integrated into the curriculum and extracurricular activities. This implementation effectively creates a harmonious and inclusive learning environment, successfully fostering student character with integrity and creativity. This study concludes that a genuinely lived model of prophetic leadership can serve as an inspiration for other Islamic educational institutions in shaping future leaders.